2012
DOI: 10.1021/ml200278u
|View full text |Cite
|
Sign up to set email alerts
|

Heteroaromatic Moieties in the Sphingosine Backbone of α-Galactosylceramides for Noncovalent Interactions with CD1d

Abstract: A series of α-GalCer analogues containing heterocyclic and aromatic moieties in the sphingosine backbone were synthesized to improve the selectivity in the Th1/Th2 cytokine profile via noncovalent interaction with three aromatic residues at the binding pocket of CD1d. In vitro and in vivo biological evaluations revealed the treatment of α-GalCer analogue (6) induced the selective stimulation of natural killer T cells to facilitate the secretion of Th2 cytokines.KEYWORDS: α-Galactosylceramide, CD1d, selectivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 26 publications
(55 reference statements)
0
15
0
1
Order By: Relevance
“…Therefore, we studied the systematic structural modification of α-GalCer to selectively polarize either the T H 1 or T H 2 immune response. For example, we recently described a series of α-GalCer analogs containing heterocyclic and phenyl moieties in the sphingosine backbone and found that treatment with a T H 2-biased α-GalCer analog selectively stimulates the secretion of anti-inflammatory cytokines in iNKT cells ( Figure 1 ) [25] , [26] . With this selective T H 2-biased α-GalCer analog in hand, we envisioned the development of new α-GalCer-based anti-inflammatory agents that control microglial activation as a potential therapy for neurodegenerative diseases.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, we studied the systematic structural modification of α-GalCer to selectively polarize either the T H 1 or T H 2 immune response. For example, we recently described a series of α-GalCer analogs containing heterocyclic and phenyl moieties in the sphingosine backbone and found that treatment with a T H 2-biased α-GalCer analog selectively stimulates the secretion of anti-inflammatory cytokines in iNKT cells ( Figure 1 ) [25] , [26] . With this selective T H 2-biased α-GalCer analog in hand, we envisioned the development of new α-GalCer-based anti-inflammatory agents that control microglial activation as a potential therapy for neurodegenerative diseases.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike our previous report [25] , we aimed to introduce various alkyl moieties in the sphingosine backbone at the late stage of synthesis via simple N- alkylation of pyrazole. The key intermediate 13 can be prepared from commercially available d -galactal in eight steps with a 12% overall yield ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3,27 Briefly, HMNCs were incubated with individual α-GalCer analogues (25 nM) for 72 h, and the effects of these analogues on cytokine induction levels were detected by ELISA. 28,29 Prototype α-GalCer was used as a positive control. The bioassay results of each analogue were compared to that of the positive control, α-GalCer, along with that of OCH (Figure 1a), known as the Th2-biasing ligand, 30 for comparison.…”
Section: Acs Medicinal Chemistry Lettersmentioning
confidence: 99%